The direct measurement of the interfacial composition of surfactant/polymer mixed layers at the air-water interface using neutron reflection - Lu, JR; Blondel, J; Cooke, D; Thomas, R; Penfold, J (1996)
The coverage and structure of caesium dodecyl sulphate (CsDS) and polyethylene oxide (PEO) in mixed monolayers formed at the air-water interface have been determined directly using neutron reflection in combination with deuterium labelling. At a fixed PEO concentration of 0.1 wt%, the variation of surface tension with concentration of CsDS showed two discontinuities, the first (X1) corresponding to the onset of formation of surfactant/polymer aggregates and the second (x2) corresponding to the onset of formation of pure surfactant aggregates. Neutron reflection has shown that there is a sharp decrease in the surface excess of PEO (Γp) with surfactant concentration, Γp reaching zero at X1. The surface excess of CsDS was found to increase smoothly through the whole concentration range tending to a limit of 4.3 × 10-10 mol cm-2. the limiting value for pure CsDS solutions. The results suggest that there is no significant interaction between surfactant and polymer at the interface and that the surface composition is determined by simple competitive adsorption.